The Influence of Brand Awareness and Social Media Marketing on Purchase Intention through Brand Trust - Marviola Hardini; Qurotul Aini; Fitra Putri Oganda; Sheila Aulia Anjani; Richard Andre Sunarjo (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2026)
The rapid development of digital technology has transformed how businesses interact with consumers, making brand awareness is an important strategy to strengthen brand presence and influence consumer behavior in online environments. In increasingly competitive digital markets, companies must build strong and credible brand images to foster consumer confidence and encourage purchasing decisions. This study aims to analyze the effect of brand awareness on purchase intention through brand trust as a mediating variable. A quantitative research approach is employed using a survey method to collect data from 135 consumers who interact with brands through digital platforms, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between brand awareness, brand trust, and purchase intention. The results of the study reveal that brand awareness has a significant positive effect on brand trust and purchase intention, while brand trust also significantly influences consumers’ purchase intention and acts as a mediating variable between brand awareness and purchase intention. These findings indicate that effective brand awareness strategies not only improve brand visibility but also enhance consumer trust, which ultimately increases the likelihood of consumers making purchasing decisions. Therefore, this study provides theoretical contributions to the field of digital marketing by explaining the mediating role of brand trust in the relationship between digital branding and purchase intention, while also offering practical implications for businesses to strengthen digital branding strategies in order to build stronger consumer trust and improve market competitiveness in the digital era.